2022
DOI: 10.1186/s12887-022-03546-1
|View full text |Cite
|
Sign up to set email alerts
|

Emicizumab in children: bleeding episodes and outcome before and after transition to Emicizumab

Abstract: Purpose Real-world data and study data regarding therapy with Emicizumab in pediatric cohorts with haemophilia A is scarce. Especially, data on previously untreated pediatric patients (PUPs) and minimally treated patients (MTPs) are missing. Methods Thirteen pediatric patients with haemophilia A and treatment with Emicizumab were retrospectively evaluated for Annual Bleeding Rates (ABR) pre-and post-Emicizumab treatment. Safety data and data on man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The decision to start emicizumab was made after discussions with parents, considering the advantages and potential risks associated with its initiation at an early age. Although evidence is limited on emicizumab use in infants, there are emerging data from real‐world experience and observational studies that provide reassuring insights 1,7–14 . Moreover, the preliminary findings from the HAVEN 7 trial (NCT04431726) showed that emicizumab was well tolerated, safe and effective in infants with SHA ≤12 months without FVIII inhibitors 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to start emicizumab was made after discussions with parents, considering the advantages and potential risks associated with its initiation at an early age. Although evidence is limited on emicizumab use in infants, there are emerging data from real‐world experience and observational studies that provide reassuring insights 1,7–14 . Moreover, the preliminary findings from the HAVEN 7 trial (NCT04431726) showed that emicizumab was well tolerated, safe and effective in infants with SHA ≤12 months without FVIII inhibitors 15 …”
Section: Discussionmentioning
confidence: 99%
“…Although evidence is limited on emicizumab use in infants, there are emerging data from real-world experience and observational studies that provide reassuring insights. 1,[7][8][9][10][11][12][13][14] Moreover, the preliminary findings from the HAVEN 7 trial (NCT04431726) showed that emicizumab was well tolerated, safe and effective in infants with SHA ≤12 months without FVIII inhibitors. 15 Despite the early promising indications about the benefits of starting emicizumab prophylaxis at a young age, there is a need for understanding the full implications of its long-term use, particularly in terms of the risk of inhibitor development.…”
Section: Discussionmentioning
confidence: 99%
“…When hematologic prophylaxis and conservative measures are not successful [e.g., analgesics (paracetamol), cyclooxygenase-2 (COX-2) inhibitors, intraarticular injections of hyaluronic acid and corticosteroids, Physical and Rehabilitation Medicine, orthoses, chemical synovectomy, radiosynovectomy], and joint-preserving surgery (e.g., arthroscopic synovectomy to control synovitis at any joint, removal of the distal tibia osteophyte by open surgery or by arthroscopic surgery at the ankle, ankle joint distraction, joint debridement by arthroscopic surgery at the knee and ankle), the only surgical solution will be ankle arthrodesis or total ankle arthroplasty at the ankle joint, and total joint arthroplasty at the elbow, knee and hip joints [14]. Table 1 summarizes the main orthopedic surgery techniques used in PWH and their indications [12–51].…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Several authors have reported that surgery can be successfully carried out in PWH with inhibitors who are being treated with emicizumab, and that bypassing drugs (recombinant Factor VII activated -rFVIIa and activated prothrombin complex concentrates -aPCCs) can be utilized concomitantly both in adults and in children [49][50][51]. In the study of Kruse-Jarres et al 215 minor surgical procedures (including minor joint procedures) were performed in 115 PWH A (64 with FVIII inhibitors), and 18 major surgeries (including arthroplasty and synovectomy) in 18 PWH A (10 with Facto VIII inhibitors).…”
Section: Orthopedic Surgery In Patients With Inhibitorsmentioning
confidence: 99%
“…The reader is referred to a very thoughtful and comprehensive discussion of the debate on immune tolerance induction and treatment decision-making pertinent to previously untreated or minimally treated patients in the era of emicizumab. 47 …”
Section: Uncertain Treatment Scenarios Strategies and Benefitsmentioning
confidence: 99%